Novecento e postmodernità nella critica musicale di Fedele d'Amico. Riflessioni sul metodo storiografico di un corso universitario - Raffaele Pozzi (LED Edizioni Universitarie, 2019)
The article examines a university course held in 1978 by the music critic Fedele d'Amico (Rome, 1912 - Rome, 1990) at the Faculty of Letters of the University of Rome La Sapienza. The course offers a reading of the twentieth century, through the analysis of the main movements and composers of the first half of the century, highlighting the historiographical method and the teacher's critical positions. The historiographical method of Fedele d'Amico attempts to identify the dominant character of the twentieth century through a comparison with nineteenth-century music. This character resides, according to d'Amico, in the general tendency of 20th century composers to be «anti-nineteenth century», to mark the discontinuity with respect to the previous century. In the more radical experiences of modernity represented above all by expressionism, dodecaphony and the serial avant-garde of the Darmstadt mouvement, d'Amico underlines the destruction of the linguistic character of music which, according to him, is the foundation of understanding in musical listening. The author, emphasizing the reductionism of some of d'Amico's statements, avoids a generic charge of conservatism by relating them to the crisis of modernism and to the spread, in the criticism of the arts during the seventies, of a new postmodern image of the twentieth century.